Study Philosophy of Wound Care on DFU in an Effort of Wound Healing and Prevent Infection Based on Self-Care - Manalu, Novita Verayanti; Yunitasari, Esti; Pandin, Moses Glorino Rumambo (Syntax Literate, 2024)
Actualization of the self-care concept that affects DFU client wound healing in terms of the need for independent wound care that is able to facilitate the success of achieving client goals and preventing infections that can progress to gangrene. This literature aims to find out the study of the philosophy of DFU wound care based on independent wound care by clients. This literature study was carried out by searching scientific publications starting in 2018-2022. The databases used are PubMed, Science Direct, and ProQuest. A literature search was carried out according to the topic with four groups of keywords based on Medical Subject Heading (MeSH) and combined with the Boolean operators AND, OR and NOT, the keywords Wound Care AND DFU AND Self-Care AND Wound Healing. Results: Study of wound care for DFU clients based on self-care which is a study of ontology, epistemology, and axiology. Self-care philosophy focuses on self-ability as an active agent through a dynamic process that directs the behavior of DFU clients in caring for their own wounds to achieve wound healing. Wound care interventions are quality, evidence-based tools that support self-care and can be used with or without the direct supervision of a healthcare professional. The motivational approach is carried out to prevent negative impacts and avoid them. A holistic approach to the health and well-being of everyone, taking into account their circumstances, needs and desires throughout life, as well as the environment in which they live will improve the client's coping so that independent wound care by a DFU client will increase the efficiency of wound healing. Conclusion: The concept of wound care for DFU clients based on self-care is beneficial for families, especially for DFU clients themselves because they can be done at any time and have a better understanding and achieve their expected goals.